Automatic Quantitation of Hybridization Signals on cDNA Arrays. (June 2002) - Tahi, F.; Achddou, B.; Decraene, C.; Alibert, O.; Guiot, H.; Auffray, C.; Piétu, G.
Large-scale hybridization of simple or complex cDNA probes to cDNA clones arrayed on high-density filters is a method frequently used to determine systematically the expression profiles of thousands of genes. Hybridization signal intensities, which reflect the level of transcription of the corresponding genes, are captured on phosphor screens with an imaging system. We describe a high-throughput system, Xdots-Reader, that performs automatic detection and quantitation of each signal on hundreds of images. Reproducibility of spot detection and quantitation within filters and between filters has been assessed in analysis of more than 8 50 000 hybridization signals on 436 filters. The automatic analysis success was greater than 97%, with 424 of the 436 tested filters fully analyzed without any human intervention. XdotsReaderis available from the Software Library at www.BioTechniques. com or at http://www.lami.univ-evry. fr/~tahi/XDotsReader. It runs on SUN workstations under UNIX (SunOS or Solaris) and on PC under LINUX. No particular hardware is required, and the software is compatible with any other software. It supports the main standard image formats.